Harga Diri dan Perilaku Narsisme pengguna TikTok pada Mahasiswa - Rijal Abdillah; Widya Finda Maika (Peneliti.net, 2023)
The high intensity of using social media, especially Tiktok, is often felt by students. Students usually use Tiktok social media for self-promotion about their strengths, uniqueness, and beauty or commonly known as narcissism. One of the factors that influence it is self-esteem, where students need appreciation and respect from others when the narcissistic behavior appears. So this study aims to determine the relationship between self-esteem and narcissistic behavior of Tiktok users in college students. The sampling technique used is purposive sampling with a total of 100 respondents who are students of Bhayangkara Jakarta Raya University a social media Tiktok users. The measuring instrument used is the self-esteem and narcissistic behavior scale. The results indicated that the value of the correlation coefficient between the variables of Self-Esteem and Narcissistic Behavior is -0.384 with a significance level (p) of 0.000 (p <0.05), so it can be stated that there is a relationship between the variables of Self-Esteem and Narcissistic Behavior Tiktok users at Bhayangkara Jakarta Raya University students.